Incidence of Grapevine Leafroll Associated Viruses -1, -2, and -3 in Mendoza vineyards - Lanza Volpe, Melisa; Gomez Talquenca, Gonzalo; Engel, Esteban A.; Gracia, Olga (2017)
Viticulture is important in Argentina's economy, especially in the province of Mendoza, which is responsible for more than 75% of the crop cultivated area. In this work, we evaluated the incidence of Grapevine leafroll-associated viruses (GLRaV) -1, -2, and -3 in Vitis vinifera clones of cultivars Cabernet Sauvignon, Cabernet Franc, and Sauvignon Blanc, planted in different zones of Mendoza. The selected clones were previously reported as putatively infected by GLRaV-2. All selected samples were analyzed by DAS-ELISA for GLRaV-1,-2 and -3. GLRaV-2 was the only virus identified in all the analyzed clones. The overall infection rates were 0.6%, 18.8% and 1.2 % for GLRaV-1, 2 and 3 respectively. For the clone Cabernet Sauvignon 337, the infection rate was very high (68.3%).